Which demographic characteristics are associated with willingness to take part in recontact studies? A cross-sectional study - Zara Kayani; Andrew Willis; Safoora Gharibzadeh; Kamlesh Khunti; Ash Routen (PLoS ONE, 2025)
Background Lower rates of participation in research by ethnic minority groups and socioeconomically deprived populations has led to efforts to develop recruitment strategies which aim to address this imbalance. Little is known about participation in recontact studies (where existing research participants are recruited to further studies). Identifying factors which predict rates of participation and retention is crucial to ensure the benefits of diversified recruitment are realised upon study completion. Methods This secondary data analysis utilised data from the Multi-Ethnic Lifestyle Study (MELS) which was a multi-centre study. Modified Poisson regression models were applied in Stata version 18.0 to examine differences in demographic characteristics (age, gender, ethnicity, migration status, education, employment) between existing MELS participants who did and did not consent to be recontacted for future health research, (2) consent to link study data to their health records, (3) and consent to share research data with universities and the NHS. Results A total of 6147 participants (mean age: 51.9 years, ± 17.12) were included in the analysis. Older age, higher education level (A levels or above compared to GCSEs) participants were more likely to consent to be recontacted, and to agree to link study data to their health records. South Asian participants were less likely to consent to recontact (PR = 0.79, 95% CI [0.71–0.88], p < 0.001) and data linkage (0.72, 95% CI [0.64–0.82], p < 0.001) compared to White participants. As the number of long-term conditions increased, so did the likelihood of consenting to re-contact (PR = 1.14, 95% CI [1.04–1.23], p = 0.002) and data linkage (PR = 1.13, 95% CI [1.04–1.22], p = 0.003). For data linkage, participants who were not born in the UK, compared to UK born participants, were less likely to consent to having their data linked to health records, although the difference was not statistically significant (PR = 1.06, 95% CI [0.94–1.20], p = 0.316). Conclusions Our findings highlight that willingness to participate in health research studies, consent to data linkage, and data sharing varies across demographic groups. Inclusive recruitment and retention strategies must be developed to encourage participation and retention in follow-up studies, especially among historically underserved groups.